Melacak Pemikiran Poskolonialisme Sartre: Pengantar Sartre untuk The Wretched of the Earth Karya Fanon - Toto Suharto (UIN Sunan Kalijaga Yogyakarta, 2011)
The article seeks to discuss Jean-Paul Sartre’s idea on Post-colonialism. The focus is on Sartre’s notion listed in Preface for Franz Fanon’s The Wretched of the Earth. Sartre stated that colonialism opposed humanism, since human beings came into the world in a free stance. Colonialism should be challenged with decolonization, aimed at revitalizing awareness of humanism obstructed by European monsters. Europe as the West, should not conduct violence and cruelty to Third world—the East. The West and the East, indeed, should not be confronted. This serves as a historical framework led to the emergence of first phase of Postcolonialism idea.